Cumulative Antimicrobial Susceptibility Data of Pseudomonas Aeruginosa Isolates from Cystic Fibrosis Patients: 4-Year Experience - KARAHASAN, AYŞEGÜL; KARADAĞ, BÜLENT TANER; FİDAN, EBRU; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (GEORG THIEME VERLAG KG, 2021)
Objective Pseudomonas aeruginosa is the most important cause of lung infection among cystic fibrosis (CF) patients, and to reduce the severity of the infection, facility-specific cumulative antibiograms could help clinicians in empirical treatment. Methods Respiratory samples of CF patients between January 2015 and December 2018 were scanned through Laboratory Operating System retrospectively. Demographical data of patients, culture results, and antibiotic susceptibilities are recorded using Microsoft Excel 2010. Cumulative antibiogram data were obtained according to the CLSI M39A4 document. Results The number of registered patients has increased in 4 years from 154 to 253. The mean age of patients varied from 9 to 11.7 (range, 2-42). The ratio of patients with a positive culture for P. aeruginosa increased from 32 to 40%, and the mean patients' age decreased from 16.6 to 11.1 (p < 0.05). A total number of 4,146 respiratory samples were analyzed. Sputum samples consisted of 42.5% (n: 1,767) of the samples with a 58.4% isolation rate of P. aeruginosa (n: 1,034). A notable increase of resistance was seen almost all antimicrobials tested by years. The ratio of multidrug-resistant (MDR) P. aeruginosa was 4.1, 10.2, 4.5, and 8.6% in 2015, 2016, 2017, and 2018. Conclusion Antimicrobial resistance is a challenging problem in CF patients, and surveillance should be done regularly.
Keywords: cystic fibrosis; Pseudomonas aeruginosa; cystic fibrosis; respiratory samples; INFECTIONS; RESISTANCE; MANAGEMENT; CHILDREN; TURKEY